Research on fabrication technology of PVV-5AVN explosive for explosive reactive armor - Pham Kim Dao; Pham Van Toai; Pham Quang Hieu; Bui Anh Thuc; Tran Van Phuong (Journal of Military Science and Technology, 2024)
PVV-5AVN explosive is a type of polymer-bonded explosive (PBX that typically comprises a mixture of RDX (hexogen), a high-explosive compound, and a polymer binder such as polyisobutylene. It finds extensive application in various generations of explosive reactive armor. This study investigates factors influencing the quality and specifications of PVV-5AVN explosives, including solvent choice, solvent ratio, mixing time, and ingredient proportions. Specifically, the RDX content is 85 ÷ 91%, and the binder system content is 9 ÷ 15% (with a DOS/PIB mass ratio of 2.75). These findings establish a fabricating process for laboratory-scale PVV-5AVN explosives that meets technical standards comparable to existing literature.